“Bir safevi devri mushafının tezyini yönden değerlendirilmesi” - Sancaktutan, Necati (My University, 2010)
Yazma eserler içerisinde, tezyinatın yoğunluklu olarak iĢlendiği eserler, Mushaf-ı Ģeriflerdir. Bu sebeple, tezyinatın tarih boyunca taĢımıĢ olduğu özellikleri ve üslup farklılıklarının en iyi Ģekilde müĢahade edilebileceği eserler mushaflardır. Tezimizin konusunu teĢkil eden „Safevî Devri Bir Mushafın Tezyini Yönden Ġncelenmesi‟ndeki amaç da, oluĢan bu farklılıkları tespit edebilmektir. ÇalıĢmamızda mushafın yapısal özelliklerinin olabildiğince en ince ayrıntılarına kadar incelenmesi temel hedeflerimizdendir. Ayrıca inceleme yapılan mushafın muzeyyen sahifelerinin konumlarının nerelerde olduğunu, sahife düzenlenmesinde hangi ölçütlere riayet edildiğini, paftalamaların nasıl yapıldığını, hangi motif gruplarının kullanıldığını tespit etmek ve kullanılan motiflerin bir tipolojisinin çıkartılması amaçlanmıĢtır. Tezimize konu olan 16‟ncı yüzyılın son çeyreğinde yazılmıĢ ve bezenmiĢ olan mushafın ilgili dönemdeki üslup farklılıklarına dikkat çekerek, o dönemin sanatçılarından söz etmemek çalıĢmamız açısından eksiklik oluĢturabilirdi. Bundan dolayı, bu konuyu da ihmal etmemeye çalıĢtık. Bunun yanında, Safevî tezhip anlayıĢının, Osmanlı‟daki Mushaf bezemelerine etkilerine de araĢtırmamız içerisinde yer verilmiĢtir.

Among manuscripts, the copies of the Holy Koran are the best ones in which ornamental arts intensively applied. Thus, examining the copies of Koran, we can see the characteristics of ornamental arts and varieties of the illuminative styles gradually developed in the course of history. The aim of our thesis, Ornamentally Examining a Copy of Koran Written and Bedecked in the Safavid Era, is, then, to explore these varieties. One of the main targets of this study is to peruse the structural characteristics of the manuscript rigorously. Besides, we have also aimed at disclosing the locations of illuminated pages of the manuscript, determining which criteria were respected in the page layout, understanding how the segmentation processes were executed, finding which varieties of patterns are used, and finally creating a typology of the patterns applied in the manuscript. Examining a copy of Koran written and ornamented in 16th century and emphasizing the varieties of illuminative styles of the century undoubtedly require a brief explanation of the artisans lived in this era. Hence, we have tried not to neglect this responsibility. Moreover, in the content of our thesis, we have also secured a section about the influences of the Safavid ornamental conception on the Ottoman illuminations of the Holy Koran.
Keywords: Türk El Sanatları